miR-23a Targets Interferon Regulatory Factor 1 and Modulates Cellular Proliferation and Paclitaxel-Induced Apoptosis in Gastric Adenocarcinoma Cells - Liu, Xue; Ru, Jing; Zhang, Jian; Zhu, Li-hua; Liu, Min; Li, Xin; Tang, Hua (PLOS ONE, 2013)
MicroRNAs are a class of non-coding RNAs that function as key regulators of gene expression at the post-transcriptional level. In our previous research, we found that miR-23a was significantly up-regulated in human gastric adenocarcinoma cells. In the current study, we demonstrate that miR-23a suppresses paclitaxel-induced apoptosis and promotes the cell proliferation and colony formation ability of gastric adenocarcinoma cells. We have identified tumor suppressor interferon regulator factor 1 (IRF1) as a direct target gene of miR-23a. We performed a fluorescent reporter assay to confirm that miR-23a bound to the IRF1 mRNA 3′UTR directly and specifically. The ectopic expression of IRF1 markedly promoted paclitaxel-induced apoptosis and inhibited cell viability and colony formation ability, whereas the knockdown of IRF1 had the opposite effects. The restoration of IRF1 expression counteracted the effects of miR-23a on the paclitaxel-induced apoptosis and cell proliferation of gastric adenocarcinoma cells. Quantitative real-time PCR showed that miR-23a is frequently up-regulated in gastric adenocarcinoma tissues, whereas IRF1 is down-regulated in cancer tissues. Altogether, these results indicate that miR-23a suppresses paclitaxel-induced apoptosis and promotes cell viability and the colony formation ability of gastric adenocarcinoma cells by targeting IRF1 at the post-transcriptional level.